The effect of extremly low frequency magnetic fields on membrane potential of lymphocytes [Çok düşük frekansli elektromanyeti̇k alanlarin lenfosi̇tleri̇n membran potansi̇yelleri̇ne etki̇si̇] - (:unkn) unknown (My University, 2008)
Objective: Although previous studies demonstrated that extremly low frequency magnetic fields (ELF-EMF) affected biologic systems, the mechanisms have not been elucidated yet. However, it is accepted that the interaction must involve the physicochemical properties of the plasma membrane. This study aimed to determine the probable change in membrane potential of mitogen induced lymphocytes exposed to ELF-EMF and correlate it with changes in proliferation of exposed cells. Methods: Lymphocytes from healthy donors were grown in RPMI medium for 72 hours, before magnetic field ( 50 Hz, 5 mT) was applied for 90 minutes. Fluorescence spectroscopy with di-4-Anepps as a probe was used to determine change in membrane potential in the the magnetic field applied and control groups. Cell count was made by cytometer using trypan blue stain. Results and Conclusion: Fluorescence spectroscopy studies revealed that magnetic field applied lymphocytes showed hyperpolarization with respect to control. A decrease in proliferation was observed in ELF-EMF exposed cells with respect to controls. These findings indicate that ELF-EMF affects membrane potential and cell proliferation.
Keywords: ELF-EMF; Hyperpolarization; Membrane potential